This is not me! Technology-identity concerns in consumers’ acceptance of autonomous vehicle technology - Wang, Xueqin (2021)
The relationship between drivers and their cars is increasingly personal, where the cars become an extension of the drivers’ self-identity. However, the penetration of autonomous vehicle (AV) technology threatens consumers’ self-identity as expressed by the act of driving. This study thus aims to examine the impacts of technology-identity concerns on consumers’ acceptance of AV technology. Theories of identity threat, identity control and innovation diffusion are synthesised to build the conceptual framework. Face-to-face interview data were collected from 353 consumers (all with a driving license) in Singapore. The results show that consumers’ technology anxiety and self-identity expressiveness act as two sources of resistance that cause consumers’ intentional avoidance of the AV technology. The avoidance is further characterised by consumers’ disengagement from the ‘observe’ and ‘try’ stages of technology penetration, which ultimately dissuades consumers’ acceptance of AV technology. The impacts of socio-demographics are also explored. Our findings contribute to multiple streams of literature and create practical implications to AV manufacturers and retailers.